Attitudes of Australian Muslims and Australian Wider Community Towards Muslim Institutions - Diallo, Ibrahima (TARBIYA: Journal of Education in Muslim Society, 2017)
Abstract Islamic (community) schools and mosques are extremely important sites for religious education, language and culture maintenance and religious rituals and practices for a large number of Muslim Australians,  These institutions remained significant and symbolic of Islamic identities despite rampant anti-Muslim sentiments:  attacks and threats against Muslim institutions (mosques and Islamic schools) and individual members of the Muslim community and negative media portrayal. Despite these hostilities and tensions, a case study conducted in Adelaide and Darwin shows that the Muslim community holds the view that the attitudes of Australian wider community toward their institutions are mixed with more positive than negative attitudes for which they blamed the media.   Abstrak Beberapa sekolah (komunitas) dan tempat peribadatan Islam  merupakan bagian yang sangat penting untuk pendidikan keagamaan, pelestarian bahasa dan budaya, dan praktik keagamaan bagi hampir semua masyarakat muslim di Australia.  Beberapa Rutinitas seperti ini masih signifikan dan menjadi simbol identitas bagi seorang muslim terlepas dari sikap sentimentil terhadap kaum muslim yang merajalela: seperti serangan dan ancaman terhadap institusi muslim (masjid dan sekolah islam), individu muslim itu sendiri dan penggambaran negatif terhadap islam itu sendiri. Terkait permusuhan dan ketegangan yang sedang terjadi saat ini, sebuah studi kasus yang dilakukan di Adelaide, dan Darwin mengemukakan bahwa komunitas muslim masih berpandangan bahwa sikap masyarakat Australia secara luas terhadap institusi mereka bercampur dengan sikap yang lebih positif daripada sikap negatif dari apa yang ditujukan oleh media.   How to Cite : Dialo, I. (2017). Attitudes of Australian Muslims and  Australian Wider Community Towards Muslim Institutions. TARBIYA: Journal of Education in Muslim Society, 4(1), 1-12. doi:10.15408/tjems.v4i1. 5830. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i1.5830